2019
DOI: 10.1038/s41415-019-0786-5
|View full text |Cite
|
Sign up to set email alerts
|

UK dental professionals' knowledge, experience and confidence when treating patients on the autism spectrum

Abstract: Background: Over 1% of the UK population have a diagnosis of autism, and yet there is minimal information regarding the experiences of dental professionals working with people on the autistic spectrum. The current study is the first to investigate UK dental professionals' knowledge of autism, their perceived confidence when treating autistic patients, and the factors that affect this. Methods: An online, self-report survey was completed by 482 UK dental professionals and included questions on participants' tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(74 citation statements)
references
References 24 publications
4
68
0
2
Order By: Relevance
“…Though this study provides a foundation for understanding autistic adults’ dental experiences in the United Kingdom, a number of questions remain. UK dental training includes special care and autism awareness lectures, yet pediatric and special care dentists are more likely to receive autism training and accept autistic patients 25,27,28 . Future research should examine if autistic people's experiences differ depending on which dentist they attend.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though this study provides a foundation for understanding autistic adults’ dental experiences in the United Kingdom, a number of questions remain. UK dental training includes special care and autism awareness lectures, yet pediatric and special care dentists are more likely to receive autism training and accept autistic patients 25,27,28 . Future research should examine if autistic people's experiences differ depending on which dentist they attend.…”
Section: Discussionmentioning
confidence: 99%
“…However, if dentists felt their education prepared them well, they were more likely to accept patients with special needs 25,26 . Other research has shown that within the United Kingdom a similar sentiment exists, with dental practitioners reporting high knowledge yet only moderate confidence when working with autistic patients 27 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies indicated a lack of formal training regarding ASD and the management of diagnosed children in terms of the available options [38,39]. On the other hand, other studies have also shown that physicians that specialized in ASD, and/or had experience with ASD scored higher in knowledge assessments regarding ASD [40,41], were able to understand the need for an early diagnosis [40,42], had a more positive attitudes towards those with ASD [40,43], and were able to better handle children with ASD in their practice [39].…”
Section: Introductionmentioning
confidence: 99%
“…Так, 97 % британских стоматологов хотя бы раз в жизни оказывали помощь пациенту с РАС. При этом 58 % врачей знали о методах и способах лечения таких пациентов, и 53,4 % смогли применить их на практике [6].…”
unclassified